Developing behavioral models of citizens for adapting to and mitigating climate change: a study on four prefectures in Japan - Aoki, Eri; Shirai, Nobuo; Baba, Kenshi; Masuhara, Naoki; Taniguchi, Makoto (Frontiers in Climate, 2024)
Individual behaviors of citizens are important for implementing the necessary measures for adapting to climate change. However, studies on the adaptive behaviors of ordinary citizens are limited. Therefore, in this study, we developed behavioral models to understand individual behaviors for adaption to and mitigation of climate change. We compared four behavior groups, namely, G1, individual mitigation; G2, individual adaptive; G3, long-term adaptive; and G4, solar-energy system installation behaviors. Following a questionnaire survey for the four behavioral groups, behavioral models were developed using structural equation modeling, which considered psychological factors along with selected attitudes, perceived effectiveness, norms, benefits, practicality, and intention. Furthermore, we considered the recognition and attribution of local climate change as key factors for adaptation behaviors toward local climate change. The behaviors of citizens in four prefectures in Japan, namely, Nagano, Tokyo, Saitama, and Kanagawa were considered. Among them, Nagano Prefecture, wherein the implementation of adaptation measures was at a low level while that of mitigation measures was at a high level, showed a differing trend. In the behavioral models, the recognition of local climate change directly affected the behavior of citizens in the individual adaptive behavior group. In both the individual adaptive and long-term adaptive behavior groups, the impact of benefits was substantial, with significant differences across local areas.Thus, effective adaptation strategies might involve tangible and familiar examples demonstrating the consequences of behavior, thus enhancing citizens' behavior evaluation perception and fostering its acceptance as a desirable behavior. Tailoring adaptation strategies to specific local contexts might also be necessity. To encourage citizens to adapt to climate change and its impacts, we propose twoway efforts, instead of providing one-way information, by supporting citizens to think about self-help and mutual help effectively. Our study can serve as a reference for future studies focusing on citizen behavior about climate change mitigation and enhance their adaptation for locally implemented strategies.